Comparisons of constitutive resistances to soybean cyst nematode between PI 88788- and Peking-type sources of resistance in soybean by transcriptomic and metabolomic profilings - Chu, Shanshan; Ma, Hui; Li, Ke; Li, Junfeng; Liu, Hongli; Quan, Leipo; Zhu, Xuling; Chen, Meiling; Lu, Wenyan; Chen, Xiaoming; Qu, Xuelian; Xu, Jiaqi; et al. (Frontiers in Genetics, 2022)
Soybean cyst nematode (SCN) is a serious damaging disease in soybean worldwide. Peking- and PI 88788-type sources of resistance are two most important germplasm used in breeding resistant soybean cultivars against this disease. However, until now, no comparisons of constitutive resistances to soybean cyst nematode between these two types of sources had been conducted, probably due to the influences of different backgrounds. In this study, we used pooled-sample analysis strategy to minimize the influence of different backgrounds and directly compared the molecular mechanisms underlying constitutive resistance to soybean cyst nematode between these two types of sources via transcriptomic and metabolomic profilings. Six resistant soybean accessions that have identical haplotypes as Peking at Rgh1 and Rhg4 loci were pooled to represent Peking-type sources. The PI88788-type and control pools were also constructed in a same way. Through transcriptomic and metabolomics anaylses, differentially expressed genes and metabolites were identified. The molecular pathways involved in the metabolism of toxic metabolites were predicted to play important roles in conferring soybean cyst nematode resistance to soybean. Functions of two resistant candidate genes were confirmed by hairy roots transformation methods in soybean. Our studies can be helpful for soybean scientists to further learn about the molecular mechanism of resistance to soybean cyst nematode in soybean.